PREPARING PEACH SEED FOR OIL EXTRACTION AND IMPROVING OIL EXTRACTION THROUGH PRESSING - Madaminova, Zilola; Khamdamov, Anvar; Xudayberdiyev, Absalom (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
This article discusses the technical technologies for preparing peach seeds for oil extraction before obtaining oil from peach fruit seeds. In other words, before extracting oil from peach seeds, the seeds need to be processed: cleaning the seeds, adjusting seed moisture, cracking the seeds, and grinding the seed kernel. The article also covers the methods of oil extraction from peach kernels using hot and cold pressing, explaining the processes of obtaining oil through both hot and cold pressing. The impact of hot pressing and cold pressing on samples of the same size and moisture content is also analyzed, with results shared.